Orientational order parameter in CO2-based alloys with rare gases from THEED data: pure CO2: Classical Cryocrystals - Danchuk, V.V.; Solodovnik, A.A.; Strzhemechny, M.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Using the transmission high-energy electron diffraction technique, we studied the temperature dependence of the diffraction reflection intensities from the solid phase of CO2. To deduce absolute values of the orientational order parameter, we modified the existing reconstruction method to account for the triatomic shape of the molecule. It is shown that for triatomics solids a higher-rank order parameter, n4, is important and cannot be neglected. Application of the modified approach yielded n, and n4, values as a function of temperature over the range from 6 to 70 K. Both orientational order parameters proved to be a nonmonotone function of temperature.